Synoptic flow patterns and decadal variations of wind‐induced mixing over western Long Island Sound. Issue 20 (29th October 2015) - Bratton, Sean D.; Colle, Brian A.; Wilson, Robert E.
Abstract: This study describes the large‐scale atmospheric flow patterns that favor mixing events within western Long Island Sound (wLIS) and how interannual and interdecadal variations in surface winds relate to bottom dissolved oxygen (DOb) variability. DOb data from the wLIS Coastal Observing System buoy were used in conjunction with the surface winds at La Guardia Airport and National Buoy Data Center buoy to identify criteria for water column ventilation and mixing from June to September. It is shown that mixing for a 36 h period after onset is favored when a majority of the surface wind observations for a day (starting at 00 UTC) are from 30° to 110° (NE to ESE) and ≥ 4 m s −1 . This criterion was used to develop a synoptic climatology and the trend in potential mixing events from 1950 to 2009. These mixing events were categorized based on three synoptic patterns: high pressure, low pressure, and a hybrid high and low. High‐pressure patterns, which include a hybrid system with a high building from the north/west and low to the south, result in the largest percentage of potential mixing events (76.9%). The number of potential mixing events increases from the 1950s to 1990s (full season and July–August) primarily from an increasing number of high‐pressure systems; however, the seasonal DOb decreased during this period. There was a slight decrease in the number of July–August potential mixing events from 1990 to 2009, mainly from a decrease in the number of low‐pressure systems. Key Points: Atmospheric flow patterns favoring mixing in western Long Island Sound are shown High‐pressure patterns result in the largest number of mixing events The number of potential mixing events per decade increased while DOb decreased